Extreme Weather and Long-term Health: Evidence from Two Millennia of Chinese Elites - Wang-Sheng Lee; Ben G. Li (Institute of Labor Economics (IZA), 2019)
Modern technology empowers human beings to cope with various extreme weather events. Using Chinese historical data, we examine the impact of extreme weather on long-term human health in an environment where individuals have no access to modern technology. By combining life course data on 5,000 Chinese elites with historical weather data over the period 1-1840 AD, we find a significant and robust negative impact of droughts in childhood on the longevity of elites. Quantitatively, encountering three years of droughts in childhood reduces an elite's life span by about two years. A remarkably important channel of the childhood drought effect is the deterioration of economic conditions caused by droughts.
Keywords: I15; N35; 330; longevity; weather; early-life conditions; elites; history of China